2020
DOI: 10.1038/s41598-020-69142-4
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound analysis, a new tool in the quest for preterm birth prediction—an observational cohort study

Abstract: Preterm birth is the leading cause of death worldwide in children under five years. Due to its complex multifactorial nature, prediction is a challenge. current research is aiming to develop accurate predictive models using patient history, ultrasound and biochemical markers. Volatile organic compound (Voc) analysis is an approach, which has good diagnostic potential to predict many disease states. Analysis of VOCs can reflect both the microbiome and host response to a condition. We aimed to ascertain if VOC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Lacey et al ( 46 ) showed that VOC analysis of vaginal swabs obtained in the mid trimester, has potential in the prediction of preterm delivery, with a sensitivity of 0.66 (95%CI 0.56–0.75) and specificity 0.89 (95%CI 0.82–0.94). However, in order to validate the e-nose as a diagnostic tool, studies using elaborate techniques such as liquid chromatography and mass spectrometry, allowing for detection of individual VOC molecules rather than the pattern-recognition based are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Lacey et al ( 46 ) showed that VOC analysis of vaginal swabs obtained in the mid trimester, has potential in the prediction of preterm delivery, with a sensitivity of 0.66 (95%CI 0.56–0.75) and specificity 0.89 (95%CI 0.82–0.94). However, in order to validate the e-nose as a diagnostic tool, studies using elaborate techniques such as liquid chromatography and mass spectrometry, allowing for detection of individual VOC molecules rather than the pattern-recognition based are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings indicate that the UP infection can be detectable with good accuracy using exhaled breath profile from 96 h onwards post-infection. The discovery of a distinct VOC profile to determine and monitor an intraamniotic UP infection extends recent clinical studies by Lacey et al in which they demonstrated that VOC testing of vaginal swabs can be used to predict group B streptococcus infection during pregnancy (45) and detect bacterial vaginosis which was linked to preterm labor (46).…”
Section: Discussion/conclusionmentioning
confidence: 71%
“…However, another recent study into prediction of PB ( 26 ), showed that VOCs from vaginal swabs obtained closest to delivery analyzed by GC-IMS were most predictive for PB with a positive predictive value of up to 86%. These results indicate that VOCs from vaginal swabs change longitudinally during pregnancy, which could also be in line with our findings of differences in VOC profiles between the different gestational categories.…”
Section: Discussionmentioning
confidence: 99%
“…Within each fold, a Wilcoxon rank sum test was used for calculating p -values in the training set to identify the important features. The 100 features with the smallest p -values were used to train different classifiers, specifically Sparse Logistic Regression, Support Vector Machine and Gaussian Process, which have been previously used in such clinical studies ( 26 ). These classifiers were applied to the test set, and this was repeated until every sample has been classified.…”
Section: Methodsmentioning
confidence: 99%